Numerical and experimental investigation of the laminar burning velocity of biofuels at atmospheric and high-pressure conditions. (1st July 2019) - Rau, F.; Hartl, S.; Hasse, C.
Highlights: The laminar burning velocity was measured with the Heat Flux method and the closed combustion vessel. Liquid biofuels, namely ethanol and iso-butanol, and the reference fuel iso-octane were investigated. The two methods show maximum deviations between 2.3 cm/s and 6.7 cm/s. The numerical mechanisms reveal prediction performances between 0.2 cm/s and 5.2 cm/s. Abstract: Premixed flame characteristics play a crucial role in most advanced combustion applications, such as gas turbines, aircraft combustors or internal combustion engines. The laminar burning velocity is one key parameter to determine the stabilisation and propagation of premixed flames. This study examined the influence of high pressures on the laminar burning velocity of biofuels and the correlation between laminar burning velocity and pressure. The investigated biofuels were pure ethanol as the state-of-the-art surrogate, pure iso-butanol as a possible alternative and several blends of ethanol/iso-octane. Due to the usage of two methods to measure the laminar burning velocity – the Heat Flux burner and the closed combustion vessel – a comparison was added for atmospheric conditions. The measured laminar burning velocities were conducted for equivalence ratios from 0.7 to 1.3, a pressure range from 1 bar(a) to 15 bar(a) and 373 K. The results were further compared to existing numerical mechanisms and literature data. The numerical mechanisms reveal prediction performances in the range of 0.2 cm/s (0.4%) and 5.2 cm/s (16.2%) for dedicated mechanisms and equivalence ratios between 0.9 and 1.1. The two methods show deviations of the laminar burning velocities between 2.3 cm/s (4.9%) and 6.7 cm/s (11.4%).